2013
DOI: 10.1017/s0952523813000394
|View full text |Cite
|
Sign up to set email alerts
|

Linking structure and function: Development of lateral spatial interactions in macaque monkeys

Abstract: Lateral spatial interactions among elements of a scene, which either enhance or degrade visual performance, are ubiquitous in vision. The neural mechanisms underlying lateral spatial interactions are a matter of debate, and various hypotheses have been proposed. Suppressive effects may be due to local inhibitory interactions, while facilitatory effects are typically ascribed either to the function of long-range horizontal projections in V1 or to uncertainty reduction. We investigated the development of lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…In addition, they demonstrated that the spatial resolution of cells in V1 (the highest spatial frequency at which cells give a response of at least 10% of its maximum) increases from birth to adulthood. There is also a general trend for increasing surround suppression from birth to adulthood (Kiorpes and Movshon, 2003 ; Chino et al, 2004 ) and facilitation develops slowly over the first year after birth (Li et al, 2013 ). These changes in receptive field size, spatial acuity and surround suppression could plausibly be attributed to changes in the geometrical sampling of neurons as their dendritic trees change shape (Sholl, 1955 ; Ferster, 1998 ; Taylor et al, 2000 ; Taylor and Vaney, 2002 ).…”
Section: Neuronal Receptive Field Properties In Postnatal Developmentmentioning
confidence: 99%
“…In addition, they demonstrated that the spatial resolution of cells in V1 (the highest spatial frequency at which cells give a response of at least 10% of its maximum) increases from birth to adulthood. There is also a general trend for increasing surround suppression from birth to adulthood (Kiorpes and Movshon, 2003 ; Chino et al, 2004 ) and facilitation develops slowly over the first year after birth (Li et al, 2013 ). These changes in receptive field size, spatial acuity and surround suppression could plausibly be attributed to changes in the geometrical sampling of neurons as their dendritic trees change shape (Sholl, 1955 ; Ferster, 1998 ; Taylor et al, 2000 ; Taylor and Vaney, 2002 ).…”
Section: Neuronal Receptive Field Properties In Postnatal Developmentmentioning
confidence: 99%
“…A behavioral study of facilitation and suppression of stimulus detection by nearby stimuli [ 103 ] concluded that facilitatory lateral spatial interactions mature late, around age 1 year. Corroborating EEG data, from visual-evoked potentials [ 104 ], showed that lateral interactions are also not mature in young human infants.…”
Section: Discussionmentioning
confidence: 99%
“…Lateral spatial interactions among objects in a visual scene can have either inhibitory or facilitative effects on visual perception. Inhibitory interactions are present at birth, suggesting they are mediated by local inhibitory processing within V1, while facilitative effects develop over the first year, suggesting they are mediated by long‐range feedback connections to V1 (Li et al, ). Similarly, the ability to discriminate textures (El‐Shamayleh et al, ) appears within months of birth.…”
Section: Structure Function and Development Of Marmoset Areas V1 Anmentioning
confidence: 99%